Funkcja SPV w procesie sekurytyzacji - Hadro, Dominika (The Function of Spy in the Securitisation Process, 2006)
Securitisation has achieved the great success both as an alternative source of capital and as a tool of assets management. One of the reasons is the possibility of adjustment of the process to legislative and market requirements of each country thanks to a construction of the transaction. One element of a construction is SPV, which eliminates the risk of initiator but also participates in other many aspects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 74-81